Comparative Evaluation of Microleakage of Glass Ionomer and Glass Ionomer with Ethanolic Extract of Propolis – An In Vitro Study - Deepti V. Balehosur; Jasmine Mary Antony; Deeksha Sharma; Vijayalaxmi Divater; Alan Winston David; Praveen Kumar Bali (Journal of Pharmacy and Bioallied Sciences)
Aim: Aim of the study is to evaluate microleakage of conventional GIC and addition of 1% ethanolic extract of propolis to conventional GIC. Methodology: A study was conducted between two groups. Group A was the conventional GIC group (control) and Group B was treated with GIC incorporated with 1% ethanolic extract of propolis (experimental). To evaluate microleakage, 15 samples were used and class V cavity preparation and restoration were done. Later, they were placed in 0.6% Rhodamine-B dye and evaluated for dye penetration under stereomicroscope. Results: Results showed that microleakage of the experimental group was decreased compared to that of the control group, but it was not statistically significant (P = 0.38).